SISTEM INFORMASI PENGOLAHAN TUGAS AKHIR BERBASIS WEB - Marsella, Minhwa Mella; Anwariningsih, Sri Huning; Charolina, Astri (Gaung Informatika, 2015)
Processing final exam project is an aspect that is very important to know the students who submitted the final  exam  project  such  as  the  title  of  the  submission  process,  filing  seminars,  and  filing  pendadaran.  The purpose  of  this  information  is  made  systems  simplify  data  processing  and  presentation  of  the  information through the website. System design methods used to design the system using an object-based system design, for making this information system using  PHP  and uses a  MySQL  database. Website produced  from this research about information processing Sahid University student thesis Surakarta. This information system is tested using black box testing, and found no problems in normal use, with these results mean the end of the task processing website otherwise good.